Influence of the Stiffness Modulus and Volume Fraction of Inclusions on Compressive Strength of Concrete. (2017) - Lie, Han Ay; Gan, Buntara Shently; Suryanto, Benny; Priastiwi, Yulita Arni
Abstract: The stiffness differences between aggregate and mortar matrix in concrete create stress concentration at their interface transition zones. Studies on 100 mm cubes with different volume and shape of inclusions, resembling aggregate particles within the concrete, suggested that it is always in this transition zone that cracks initiate. Further detailed finite element analysis brought to light that especially the mortar nodes in principal tension - compressive stresses were most vulnerable to premature failure. The study also suggested that as the relative stiffness between the inclusion and the surrounding mortar increases, the stress concentration problem increases, resulting in premature cracking and lower compressive strength, when compared to the specimens with more homogeneous stiffness profile. This study aims to investigate in more details the influence of inclusion volume fraction, compressive strength and stiffness modulus on the compressive strength of 100×100×50 mm3 prisms. The inclusions were in cylindrical shape and made of mortar with a compressive strength ranging from approximately 20 MPa to 50 MPa; the matrix was also made of mortar but with a constant compressive strength of approximately 29 MPa. It is found that the compressive strength and initial stiffness of the concrete prisms are directly related to the volume fraction and compressive strength of the inclusions. Finite element analysis is conducted to investigate the influence of the relative strength of inclusion to the surrounding mortar.